"The Boy and the Blade of Grass": trajectories of children's music making - Teca Alencar de Brito (Universidade Federal de Santa Maria, 2012)
This article relates the trajectories of children's music making to the Estética do Impreciso e do Paradoxal (Aesthetics of the Imprecise and Paradoxical), proposed by the German musician Hans Joachim Koellreutter (1915-2005) and to the concepts of musicality and sonority suggested by the French composer Pierre Schaeffer (1910-1995). Such an analysis, which is included in the doctoral thesis that I defended for the Communications and Semiotics Program at the Pontifical University of São Paulo (2007), proposes to expand discussions and thought regarding children's relationship to sounds and music, aiming to validate and signify the routes of such occurrences. Reporting back to the concept of mino literature proposed by Gilles Deleuze (1925-1995) and Félix Guattari (1930-1992), the article points towards a minor mode of thinking about/making music in early childhood: a singular mode that reveals the singularity and dynamic transformation of the ideas of music, considering the gains in complexity that surround the process of development as a whole. A mode that is captured by the great systems that are dominant in a culture's music production, as well as the territories of music education. In conclusion, I point towards the need to institute open-ended plans that dialogue with tradition, experimentation, "make believe," and, in short, plans of possibilities that permeate children's relationship to sounds and music